Catalog of the mite (Acari) type specimens deposited at the “Universidade Estadual Paulista (UNESP), Campus de São José do Rio Preto”, São Paulo, Brazil (DZSJRP) - de Araújo, Marcel Santos (2019)
A catalog of the type specimens of mites deposited at the Mite Collection of the Zoology and Botany Department of São Paulo State University (São José do Rio Preto, São Paulo state, Brazil) is presented. The collection of type specimens includes 120 species of 64 genera and 16 families, most of which from Brazil, but also from Angola, Australia, Costa Rica, Phillipines, South Africa, Sultanate of Oman and Thailand. For each species the original publication, provenance data, specimens conditions are provided.